The Impact of Working Capital on Profitability: An Empirical Study on the Jordanian Industrial Companies - Twairesh, Abdullah (The Arab Journal of Administration, 2018)
The purpose of this study is to examine the relationship between working capital management and profitability of Industrial Jordanian companies listed in Amman Stock Exchange for the 10 years period from 2003-2012 which comprises of (48) Industrial companies was finally used as sample size, The effect of different variables of working capital management have been studied including the Average collection period, Average Inventory period, Average payment period and cash conversion Cycle with controls variables on the return of assets (ROA) and return of equity (ROE) as a measures of profitability for Jordanian companies, Panel data methodology was adopted because it combined time series and cross sectional data. The method of analysis is correlations and multiple regression analysis. The result showed that working capital variables has negative and significant relationship with firm’s profitability. This implies that firms’ performance can be increased with short size of Cash Conversion Cycle, The result showed that debt ratio and current ratio have negative and significant relationship with firm’s profitability, while firm size showed positive and significant relationship with firm’s profitability, the study recommended that cash conversion cycle should be reduced and Industrial Jordanian Companies must set a trade-off between profitability and liquidity so that neither the liquidity nor profitability suffers, managing working capital in more efficient ways.